지속가능한 농업시스템 구축 연구 (2/2차연도) - 김창길 (지속가능한 농업시스템 구축 연구(2의2차년도), 2015)
This report is the final result of a two-year research project on establishing sustainable agricultural systems in Korea. In this report, numerous empirical analyses of sustainable agriculture was conducted; namely changes in soil and water resources, the nutrient balance in the farmland, the relationship between productivity and environment (based on estimation of rice production function), an integrated analysis of environment and economic efficiency and social aspect analysis. In addition, plans to establish sustainable agricultural systems were presented. These plans were based on an analysis of the contribution financial investment in fostering a sustainable agriculture that would improve the added value of agriculture, an in-depth analysis of soil nutrient management policies for professionals, an analysis of farmers’ recognition of, and inclination to practice, sustainable agriculture, and an analysis of the priorities of an implementation program based on AHP methodology. We trust that this report will constitute a useful reference in establishing more effective strategies for sustainable agricultural systems. In particular, this research is expected to be utilized as the basic data and information for making the fourth five-year (2016~2010) plan for fostering the environment-friendly agriculture in Korea.